HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS LIANG ANGGANG TAHUN 2024 - Nurjanah, Annisa; Zakiah , Hj.; Prihatanti , Nur Rohmah; Hapisah, Hapisah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: Stunting is a condition where a person's height is less than normal based on age and gender. The results of data obtained at the Banjarbaru City Health Office show that out of 9 working areas of Health Centers in Banjarbaru City, the highest stunting rate is in the Liang Anggang Public Health. Objective: To determine the relationship between exclusive breastfeeding and the incidence of stunting in toddlers in the Liang Anggang Public Health in 2024,Method: The type of analytical survey research with a case control approach, a sample of 170 cases and 170 controls of toddlers with a ratio of 1:1. The population of all toddlers aged 6-59 months was 987. Sampling technique used (Systematic Random Sampling). Stunting incidence variables and exclusive breastfeeding. Data collection was obtained from secondary data in the form of toddler cohorts. Data were analyzed used the chi square test with a significance of 0.05.Results: The results of the study showed that the incidence of stunting was 170 or (50.0%). Non-exclusive breastfeeding was 120 or (70.6%). There was a corelations between exclusive breastfeeding and the incidence of stunting in toddlers aged 6-59 months (ρ value 0.014 <0.05). OR of 0.562.Conclusion: The results of the study showed a corelations between exclusive breastfeeding and the incidence of stunting in toddlers aged 6-59 months. Therefore, it is hoped that there will be new promotive efforts to reduce the high incidence of stunting that occurs by providing health education about the importance of exclusive breastfeeding.